A new species and three records of Chloroperlidae (Plecoptera) from China - Zhang, Yao; Wang, Bingli; Yao, Gang; Li, Wenliang; Li, Weihai (Zootaxa, 2024)
A new species of the genus Suwallia Ricker, 1943, S. rostrata sp. nov., from Xizang of southwestern China is described, illustrated and compared with similar species. Alloperla kurentzovi Zhiltzova & Zapekina-Dulkeit, 1977, A. kurilensis Zhiltzova, 1978, A. teleckojensis Šámal, 1939 are reported for the first time from China. The diagnostic features of these species are illustrated with color images.